Men's perceptions about the assistance provided in primary health care - Freitas, Cilas Viana de (2021)
Objective: to identify men's perception about the assistance offered to their needs in primary health care. Method: a qualitative study, carried out with 24 male users, registered in a basic health unit of a municipality in the inland of the Northeast region. The data were collected through semi-structured interviews and analyzed using the content analysis method. Results: four categories emerged. There were disagreements regarding men's perception on the health care they received, despite most of them having a positive view. They seek the service when they are already ill, and lack of knowledge on specific actions for the male population was verified, as well as the obstacles to accessing such services. Conclusion: assistance to men's health is provided by specific actions and centered on the prostate and during the Novembro Azul (Blue November) program. It is necessary to expand treatment assistance to prevent illness and promote health.